Resistivity coefficients for body composition analysis using bioimpedance spectroscopy: Effects of body dominance and mixture theory algorithm - Ward, L.; Isenring, E.; Dyer, J.; Kagawa, Masaharu; Essex, T. (Institute of Physics Publishing Ltd, 2015)
© 2015 Institute of Physics and Engineering in Medicine. Body composition is commonly predicted from bioelectrical impedance spectroscopy using mixture theory algorithms. Mixture theory algorithms require the input of values for the resistivities of intra-and extracellular water of body tissues. Various derivations of these algorithms have been published, individually requiring resistivity values specific for each algorithm. This study determined apparent resistivity values in 85 healthy males and 66 healthy females for each of the four published mixture theory algorithms. The resistivity coefficients determined here are compared to published values and the inter-individual (biological) variation discussed with particular reference to consequential error in prediction of body fluid volumes. In addition, the relationships between the four algorithmic approaches are derived and methods for the inter-conversion of coefficients between algorithms presented.